An evaluation of a video magnification-based system for respiratory rate monitoring in an acute mental health setting. (April 2021) - Laurie, J.; Higgins, N.; Peynot, T.; Fawcett, L.; Roberts, J.
Highlights: Motions Magnification allows nurses to make accurate respirations observations over video when it was otherwise difficult. Observation over video allows mental health nurses to make observations from a distance, increasing nurse safety. This technology can be integrated into existing clinical settings. Abstract: Context: One of the most important goals of inpatient psychiatric care is to provide a safe and therapeutic environment for both patients and staff. A small number of aggressive or agitated patients are difficult to sedate, even after multiple doses of sedating antipsychotics. Adverse effects can result in harm to the patient and staff and that observations are conducted without touching the patient. Aim: This study aims to determine if motion magnification can improve the feasibility of non-contact respirations monitoring over a video feed. Methods: Registered nurses were invited to view seven pairs of pre-recorded footage of healthy volunteers and count the number of breaths that they observe over a period of one minute for each. One of the paired videos was unprocessed and the other magnified the motion of chest rise and fall. Results: Nursing observation of respirations showed an improvement in reduction of count error from 15.7 % to 1.5 % after video magnification of respiratory movement. Nurses also stated that viewing the processed video was much easier to make their observations from. Conclusion: It is possible to use magnified video to monitor respirations of patients during circumstances where it is potentially difficult to obtain. Further observational studies should be conducted on a larger scale with this type of technique and is urgently needed to inform practice.